Lexical influences in audiovisual speech perception - Brancazio, Lawrence (Journal of Experimental Psychology: Human Perception and Performance, 2004)
Phoneme identification with audiovisually discrepant stimuli is influenced by information in the visual signal (the McGurk effect). Additionally, lexical status affects identification of auditorily presented phonemes. The present study tested for lexical influences on the McGurk effect. Participants identified phonemes in audiovisually discrepant stimuli in which lexical status of the auditory component and of a visually influenced percept was independently varied. Visually influenced (McGurk) responses were more frequent when they formed a word and when the auditory signal was a nonword (Experiment 1). Lexical effects were larger for slow than for fast responses (Experiment 2), as with auditory speech, and were replicated with stimuli matched on physical properties (Experiment 3). These results are consistent with models in which lexical processing of speech is modality independent.
Keywords: *Lipreading; *Speech Perception; *Visual Perception; *Vocabulary; Adolescent; Adult; Female; Humans; Lipreading; Male; Phonetics; Reaction Time; Speech Perception; Visual Perception; Vocabulary; adolescent; adult; article; clinical trial; controlled clinical trial; controlled study; dept.psy; female; human; linguistics; lip reading; male; phonetics; randomized controlled trial; reaction time; speech perception; vision